Student and staff perceptions of alcohol as part of student life in Denmark: A Q methodology study - Christensen, Stine Holmegaard (PLoS One, 2018)
INTRODUCTION: Intervening effectively to prevent students’ harmful use of alcohol remains a challenge. Harmful alcohol use has been noted as the most dominant public health problem facing universities today. This study sought to investigate the diversity in staff and student perceptions of the contribution alcohol makes to student life in a Danish university setting. Increasing understanding of staff and students’ perceptions of how alcohol fits into student life is required to amend future public health intervention for this population. MATERIALS AND METHODS: This Q methodology study included 38 staff members and 105 students from Aarhus University, Denmark. Participants used online Q sorting software, to rank 40 statements about the contribution alcohol makes to the university student experience from strongly agree to disagree. To support the interpretation of the factors, self-reported alcohol consumption and demographic data were collected. In addition qualitative data was collected on the participant’s reasons for the ranking of the items they most strongly agreed or disagreed with. RESULTS AND DISCUSSION: Using principal components analysis, five statistically independent viewpoints for students and four for staff were identified. The findings provide evidence to inform approaches to prevent harmful alcohol use. Some viewpoints suggest a need for tailored secondary and tertiary prevention and intervention that focusses on individuals and/or sub-groups who are at risk of consuming alcohol at harmful levels. Other viewpoints suggest the need for primary universal prevention to support the maintenance of healthy norms which can prevent harmful alcohol behaviour. Public health campaigns need to ensure that interventions targeting harmful alcohol use at universities challenge problematic perceptions and attitudes while also bolstering exposure to positive norms.